The Urgency of Social Ethics in Santri Tradition at Muhammadiyah's Pesantren - Firmansyah; SA, Romli; Munir (Tafkir: Interdisciplinary Journal of Islamic Education, 2024)
This research aims to analyze the characteristics of social ethics in Santri (student) traditions, symbols and symbolic meanings of social ethics in Santri traditions, and the urgency of social ethics in the context of developing Santri traditions. The approach in this research is a case study in Pondok Pesantren Modern Al-Manar Muhammadiyah Boarding School Ogan Komering Ilir. Data collection used observation, interview, and documentation techniques. At the same time, the research data was analyzed using qualitative analysis techniques, such as the Miles & Huberman model. The results showed that the characteristics of social ethics in the Santri tradition can be identified into four forms of social action, namely instrumental rationality action, value-oriented rationality actions, traditional actions, and affective actions. As the perpetrators of the tradition, Santri only understands the Santri tradition in its theological and sociological meanings. Ustaz (teacher), as the shaper of the Santri tradition, understands the sense of tradition in various contexts, namely theological, philosophical, sociological, psychological, political, economic, and cultural. The urgency of social ethics in the context of developing the Santri tradition is as a value system in the process of forming the Santri tradition, as a code of ethics contained in the Santri tradition, and as a moral philosophy to explain the existence of the Santri tradition.